Examining the Significance of Literature in Language Learning: A Linguistics Analysis of Selected Poems for Educational Purposes - Hani, Hadiya Ahmad; Ajmal, Malik Umer; Arsalan Haider (English Lecturers and Teachers Association (ELTA), 2024)
This research delves into the profound significance of English literature in the realm of language learning, focusing on a meticulous linguistic analysis of three carefully selected poems: “Be Nobody’s Darling” by Alice Walker, “Mending Wall” by Robert Frost, and “As I Walked Out One Evening” by W. H. Auden. Through a nuanced exploration of these poems’ linguistic features, cultural contexts, and thematic elements, this study illuminates the multifaceted ways in which students can effectively learn language through literature. By closely examining vocabulary choices, syntactic structures, vivid imagery, and nuanced tones within these poems, students are provided with invaluable opportunities to deepen their language proficiency while simultaneously gaining invaluable insights into diverse cultural perspectives. Moreover, the findings underscore the inherent power of literature as a dynamic pedagogical tool, capable of offering authentic and engaging materials that not only facilitate language acquisition but also foster critical thinking skills and cross-cultural understanding. Ultimately, this research highlights the transformative potential of incorporating literature into language education, emphasizing its ability to enrich the language learning experience and cultivate well-rounded communicative competence among students. By embracing literature as an integral component of language pedagogy, educators can create dynamic learning environments that inspire and empower students to engage meaningfully with the English language and the world around them. Keywords: language learning; linguistic analysis; Educational Purposes.